Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1088/1742-6596/224/1/012030
|View full text |Cite
|
Sign up to set email alerts
|

Tidal volume (TV) post-process obtained with electrical impedance tomography on a group of chronic obstructive pulmonary disease (COPD) patients. Use of adjust equations

Abstract: Abstract. Equations used to estimate ventilation out of EIT images, validated on healthy volunteers show a significant bias and a larger variance when were applied on a COPD patients group. The differences in estimation values were found to be highly correlated with anthropometric parameters. Two groups of 13 and 4 COPD male patients (FEV1/FVC<70% and FVC ≥ 80%) were used in this study. We have measured different anthropometric parameters like age, weight, height and skinfolds. The EIT system (TIE4sys) and a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“… Bias and limits of agreement distribution in liters for tidal volume (TV) ( 37 , 39 , 47 , 49 , 52 , 53 , 55 , 58 , 64 , 65 , 71 90 ), end-expiratory lung volume (EELV) ( 36 , 37 , 87 , 91 ), forced expiratory volume in 1s (FEV 1 ) ( 26 , 27 , 64 , 69 , 74 , 92 94 ) and forced vital capacity (FVC) ( 69 , 74 , 92 , 93 ) per telemonitoring technique. Spiro; spirometry (including BbB-analyzers) in blue, RIP; respiratory inductance plethysmography in orange, RMP; respiratory magnetic plethysmography in gray, and EIT; electrical impedance tomography in yellow.…”
Section: How Accurate Are Telemonitoring Systems?mentioning
confidence: 99%
See 1 more Smart Citation
“… Bias and limits of agreement distribution in liters for tidal volume (TV) ( 37 , 39 , 47 , 49 , 52 , 53 , 55 , 58 , 64 , 65 , 71 90 ), end-expiratory lung volume (EELV) ( 36 , 37 , 87 , 91 ), forced expiratory volume in 1s (FEV 1 ) ( 26 , 27 , 64 , 69 , 74 , 92 94 ) and forced vital capacity (FVC) ( 69 , 74 , 92 , 93 ) per telemonitoring technique. Spiro; spirometry (including BbB-analyzers) in blue, RIP; respiratory inductance plethysmography in orange, RMP; respiratory magnetic plethysmography in gray, and EIT; electrical impedance tomography in yellow.…”
Section: How Accurate Are Telemonitoring Systems?mentioning
confidence: 99%
“…Only a few studies investigated the accuracy of volumetric measurements with EIT compared to spirometry. Balleza et al ( 88 , 89 ) Marco et al ( 90 ) studied differences between EIT and spirometry in multiple populations and found biases for TV between −0.003 L and 0.218 L. Ngo et al ( 64 ) found a bias of 0.243 L for TV. Sosio et al ( 65 ) found a bias of −0.095L.…”
Section: How Accurate Are Telemonitoring Systems?mentioning
confidence: 99%